Approaches to sustainability decision making in product development projects and portfolios - Martinsuo, Miia (Edward Elgar Publishing, 2025)
Decisions in product development deal with finding the products and services that have the best potential to succeed on the market. Companies themselves, their customers, and the society in general are increasingly pursuing environmental sustainability, so there is a need to understand how sustainability can be taken into account in the decision making of product development projects. This chapter explores sustainability-related decision-making concerning product development projects and portfolios in a study of three companies that have a strategic interest to increase environmental sustainability in their business. The findings reveal two main approaches, here written into vignettes of strategy and compliance guiding sustainability decision making. Since all companies explicated both approaches, they were combined and together cover four decision domains of sustainability decision making in product development projects: direction, scope, content, and changes. The findings show that sustainability needs to be treated holistically in all phases of the decision-making process and adds a powerful external and regulatory connection to managing product development projects and portfolios. The institutional embeddedness of product development generates a need to integrate regulatory issues and aggregate customer and stakeholder voices as part of the decision-making processes.
Research Handbook on Sustainable Project Management